Estratégias de promoção da saúde no território escolar: diálogos entre o Brasil e Portugal - Magalhães, Maria Araci (2012)
The curative medicine associated with the intense process of reconstruction and transformations of geographic space as well as the economic, social and cultural conditions which affect populations, afforded by the advent of industrialization and globalization have forced the population growth and excessive swelling of the cities. These changing circumstances have enabled the gradual increase in life expectancy, the aging population and chronic degenerative diseases to raise costs for the sectors of health. In this context, the objective of this study is to analyze the relevance of health promotion programs near the school populations, as well as school health promotion training adopted in Portugal and Brazil aimed at improving quality of life through knowledge and action. For this purpose, was produced an intensive literature review that supports the proposition of the integrated management system within the health education using participatory research as a tool for promotion of population health in the school environment.